Powder Spread Process Monitoring in Polymer Laser Sintering and its Influences on Part Properties - Klippstein, Sven Helge; Heiny, Florian; Pashikanti,, Nagaraju; Gessler, Monika; Schmid, Hans-Joachim (JOM - The Journal of The Minerals, Metals & Materials Society (TMS))
Confidence in additive manufacturing technologies is directly related to the predictability of part properties, which is influenced by several factors. To gain confidence, online process monitoring with dedicated and reliable feedback is desirable for every process. In this project, a powder bed monitoring system was developed as a retrofit solution for the EOS P3 laser sintering machines. A high-resolution camera records each layer, which is analyzed by a Region-Based Convolutional Neural Network (Mask R-CNN). Over 2500 images were annotated and classified to train the network in detecting defects in the powder bed at a very high level. Each defect is checked for intersection with exposure areas. To distinguish between acceptable imperfections and critical defects that lead to part rejection, the impact of these imperfections on part properties is investigated.

Powder Spread Flaws in Polymer Laser Sintering and its Influences on Mechanical Performance - Klippstein, Sven Helge; Schmid, Hans-Joachim (Proceedings of the 33nd Annual International Solid Freeform Fabrication Symposium)
By monitoring the recoating process within polymer laser sintering production, it was shown that multiple powder-spread-flaws can be detected. Those groove-like flaws are expected to be the result of agglomerates jamming between the recoater and the last powder layer. This work is analyzing the interaction between powder-spread-flaws and part properties, showing the influence of the recoating process on the performance of laser sintering parts. Therefore, artificial powder-spread-flaws are applied to the build jobs of tensile test specimens which are measured and analyzed regarding the elongation at break, strength and fracture position. For the characteristics of the flaws, the artificial grooves are varied in depth and width. Furthermore, the position of the flaw is changed form mid part to close to surface areas. It was shown, that several flaws are visible at the part surface, resulting in stress concentration and reduced performance. But there are as well parts with flaw-layers, which are not visible after the build process on the part. Those parts can have significantly reduced mechanical properties as well.
Keywords: Selective Sasersintering; Process Monitoring; Powder Spread

A Shape Newton Scheme for Deforming Shells with Application to Capillary Bridges - Schmidt, Stephan; Gräßer, Melanie; Schmid, Hans-Joachim (SIAM Journal on Scientific Computing)
Keywords: Applied Mathematics; Computational Mathematics

Low Temperature Laser Sintering with PA12 and PA6 on a Standard System - Menge, Dennis; Schmid, Hans-Joachim (Macromolecular Symposia)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Innendrückwalzen – Ein innovatives Umformverfahren zur inkrementellen Formgebung von wanddickenkonturierten Rohren mit lokal einstellbaren mechanischen Eigenschaften - Wiens, Eugen

Creation of a Knowledge Space by Semantically Linking Data Repository and Knowledge Management System - a Use Case from Production Engineering - Scheveleva, Tatyana; Wawer, Max Leo; Oladazimi, Pooya; Koepler, Oliver; Nürnberger, Florian; Lachmayer, Roland; Auer, Sören; Mozgova, Iryna

Knowledge Annotation within Research Data Management System for Oxygen-Free Production Technologies - Mozgova, Iryna; Altun, Osman; Scheveleva, Tatyana; Castro, Andre; Oladazimi, Pooya; Koepler, Oliver; Lachmayer, Roland; Auer, Sören

Comparative Evaluation of Product and Service Solutions in the Context of Product-Service Systems and Technical Inheritance - Schneider, Jannik; Scheidel, Wieben; Wurst, Johanna; Mozgova, Iryna; Lachmayer, Roland

Quantification of the material-related environmental impact of topology-optimized multi-material components - Herrmann, Kevin; Bode, Behrend; Wurst, Johanna; Gembarski, Paul; Mozgova, Iryna; Lachmayer, Roland

Sustainability Assessment of Products manufactured by the Laser Powder Bed Fusion (LPBF) Process - Wurst, Johanna; Mozgova, Iryna; Lachmayer, Roland

Life cycle cost impact of maintenance networks for product-service system fleets - Schneider, Jannik; Mozgova, Iryna; Lachmayer, Roland

Procedure to Create an Automated Design Environment for Functional Assemblies - Altun, Osman; Kutay, Y; Mozgova, Iryna; Lachmayer, Roland

Ontology-Based Documentation of Quality Assurance Measures Using the Example of a Visual Inspection - Sheveleva, Tatyana; Herrmann, Kevin; Wawer, Max Leo; Kahra, Christoph; Nürnberger, Florian; Koepler, Oliver; Mozgova, Iryna; Lachmayer, Roland; Auer, Sören

Technical Inheritance as an Approach to Data-Driven Product Development - Lachmayer, Roland; Mozgova, Iryna (Design Methodology for Future Products)

Corporate Strategy Based Quantitative Assessment of Sustainability Indicators at the Example of a Laser Powder Bed Fusion Process - Wurst, Johanna; Schneider, Jannik; Ehlers, Tobias; Mozgova, Iryna; Lachmayer, Roland

Parametrization of a Hybrid Component Production Process Chain Based on Semantically Annotated Data. - Wawer, Max Leo; Sheveleva, Tatyana; Koepler, Oliver; Nürnberger, Florian; Mozgova, Iryna

Normalization Matrix for Sustainability Assessments Considering the Laser Powder Bed Fusion Process - Wurst, Johanna; Mozgova, Iryna; Lachmayer, Roland

Management of Research Field Data Within the Concept of Digital Twin - Dierend, Hauke; Altun, Osman; Mozgova, Iryna; Lachmayer, Roland

Morita theory for non-commutative noetherian schemes - Burban, Igor; Drozd, Yu. (Advances in Mathematics)
In this paper, we study equivalences between the categories of quasi–coherent sheaves on non–commutative noetherian schemes. In particular, we give a new proof of Căldăraru's conjecture about Morita equivalences of Azumaya algebras on noetherian schemes. Moreover, we derive necessary and sufficient condition for two reduced non–commutative curves to be Morita equivalent.

On elliptic solutions of the associative Yang-Baxter equation - Burban, Igor; Peruzzi, A. (Journal of Geometry and Physics)